The Use of Domino Reactions for the Synthesis of Chiral Rings - Pellissier, Hélène (Synthesis, 2020)
This short review highlights the recent developments reported in the last four years on the asymmetric construction of chiral rings based on enantioselective domino reactions promoted by chiral metal catalysts.1 Introduction2 Formation of One Ring Containing One Nitrogen Atom3 Formation of One Ring Containing One Oxygen/Sulfur Atom4 Formation of One Ring Containing Several Heterocyclic Atoms5 Formation of One Carbon Ring6 Formation of Two Rings7 Conclusion
Keywords: chiral rings; enantioselective domino reactions; enantioselectivity; asymmetric metal catalysis; chirality